Formation of oxygen bubbles and its influence on current efficiency in micro-arc oxidation process of AZ91D magnesium alloy - Guo, Hongfei; An, Maozhong; Xu, Shen; Huo, Huibin (Thin solid films, 2005)
Micro-arc oxidation (MAO) of metals is a complicated process combining concurrent partial process of oxide film formation, dielectric breakdown, dissolution of pre-existing film and anodic gas evolution. The probability of domination for any of these partial processes in the overall process depends on the nature of the substrate metal, the constituents and concentration of the electrolyte, as well as on the applied current density. Thus, MAO is an energy-consumption process, always accompanied by plasma chemical, electrochemical and physics chemical reactions in the micro-arc discharge channels. Under those circumstances the subject of current efficiency becomes very important. The primary objective of this study is to evaluate the oxide film growth efficiency during MAO process. A series of experiments based on different operating conditions have been performed and the current efficiency has also been calculated. The possible reasons leading to the low current efficiency have also been evidenced as anodic oxygen gas evolution, metal anodic dissolution and chemical dissolution of pre-existing oxide films in the electrolyte. Among these reasons oxygen gas evolution associated with electronic current during sparking is considered to be the dominating one for the low current efficiency, and the factors contributing to formation of oxygen bubbles have also been categorized.